2009
DOI: 10.1002/bit.22217
|View full text |Cite
|
Sign up to set email alerts
|

Development of mammalian production cell lines expressing CNTO736, a glucagon like peptide‐1‐MIMETIBODYTM: Factors that influence productivity and product quality

Abstract: In an attempt to develop a high producing mammalian cell line expressing CNTO736, a Glucagon like peptide-1-antibody fusion protein (also known as a Glucagon like peptide-1 MIMETIBODY), we have noted that the N-terminal GLP-1 portion of the MIMETIBODY was susceptible to proteolytic degradation during cell culture, which resulted in an inactive product. Therefore, a number of parameters that had an effect on productivity as well as product quality were examined. Results suggest that the choice of the host cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…The relative values of protein abundance were estimated by spectral counting method, followed by normalized spectral abundance factor (NSAF) method for reliable normalization20. Since large proteins usually tend to contribute more to the ‘peptide/spectra’ than small ones, the NSAF method is useful to minimize the variations originated from protein length.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative values of protein abundance were estimated by spectral counting method, followed by normalized spectral abundance factor (NSAF) method for reliable normalization20. Since large proteins usually tend to contribute more to the ‘peptide/spectra’ than small ones, the NSAF method is useful to minimize the variations originated from protein length.…”
Section: Resultsmentioning
confidence: 99%
“…The fragmentation of therapeutic proteins by HCPs in the culture supernatants has been observed in rCHO cells producing mAbs9, Fc-fusion proteins71920, interferon γ21, factor VIII8, and erythropoietin (EPO)22. Cathepsins in the culture supernatants have been reported as enzymes that break down proteins23242526.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the intact antibody (Ab) molecules that are remarkably resistant to proteolytic clipping, glycoproteins, due to their relatively exposed three‐dimensional structure, can be exquisitely sensitive to proteases and other degradative activities (Varki et al,1999). We and others have previously demonstrated that there is a correlation in the amount of glycosylation to the degree of susceptibility to proteases (Dorai et al,2009; Rutledge and Enns,1996). In fact, this knowledge is used in designing a longer lasting Aranesp (Elliott S et al,2003) or Enbrel with extended circulating half‐life (Gottlieb and Bos,2002).…”
Section: Introductionmentioning
confidence: 77%
“…Table 2 shows that the amount of serine protease present in the spent medium ranged from less than 0.2 pg/mL to more than 380 pg/mL but there was no correlation of the amount of N‐terminal clipping to the level of serine proteases present. For example, very little if any clipping could be detected in CNTO736 expressed in myeloma cell lines NS0 and Sp2/0 (Dorai et al,2009), but these host cell lines accumulate serine proteases that are comparable with that of CHOK1SV derived clones. Moreover, three different clones of CHOK1SV expressing CNTO736, namely, A37 (C1672C), B3, and C64 (C1352C), which had significantly different amounts of N‐terminal clipping, had comparable levels of serine proteases (Figure 2B and Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation